Transplant Tourism to China: The Impact on Domestic Patient Care Decisions - Biggins, Scott W. (2009)
Organ procurement in China has been criticized because of its reliance on executed prisoners as donors. We aimed to assess the influence of perceptions about organ procurement practices in China on domestic patient care decisions. METHODS: An anonymous Internet administered case-based questionnaire was used to survey an sample of healthcare professionals with affiliations to hepatology and transplantation professional societies. RESULTS: Of 674 completed surveys, the vast majority (93%) of the respondents were physicians, surgeons or allied transplant professionals actively caring for liver transplant patients and 81% practiced in the United States (US). A strong majority believed procurement practices were ethically sound in the US and Europe (87% and 73%) but fare fewer believed that procurement practices were ethically sound in China (4%, p<0.001). In case-based questions, lack of confidence in the ethical standards of organ procurement in China predicted patient-care decisions. The majority would provide post-transplantation care for patients who underwent liver transplantation at another domestic center, in a foreign country and in China (90%,78%,63%, respectively, p<0.001) yet respondents who suspected unethical procurement practices in China were more reluctant to do so (p<0.001). CONCLUSIONS: Transplant professionals expressed concern about organ procurement practices in China which influenced their patient care decision-making.